2005
DOI: 10.1111/j.1553-2712.2005.tb00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Emergency Contraception in Massachusetts Emergency Departments

Abstract: There was significant variability in access to EC in Massachusetts EDs and in services for sexual assault survivors. Hospital type and provider preference affected availability. This study suggests that access to EC is limited, and that there are not consistent services for women seeking EC, including for victims of sexual assault.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…management of ectopic pregnancy and miscarriage; [3][4][5][6][7][8][9][10] furthermore, referral practices for family planning services vary across sites. 11 Advocates for Catholic health care facilities argue that women should know that restrictions on reproductive health care exist at these facilities because this is part of Catholic identity.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…management of ectopic pregnancy and miscarriage; [3][4][5][6][7][8][9][10] furthermore, referral practices for family planning services vary across sites. 11 Advocates for Catholic health care facilities argue that women should know that restrictions on reproductive health care exist at these facilities because this is part of Catholic identity.…”
mentioning
confidence: 99%
“…[15][16][17] However, health care systems have used various strategies after mergers to continue to off er reproductive health care services, 16,17 and there is evidence that certain services prohibited by the directives are provided within Catholic health care facilities. [3][4][5]7,10 Given this tension between the increasing reach of the directives and attempts to provide comprehensive women' s health care, it is important to understand the state of access to a range of ambulatory family planning services at Catholic hospital clinics. Prior studies have demonstrated that most women anticipate similar access to family planning services at Catholic and non-Catholic institutions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unprotected sex, outside the setting of rape, was not considered an "emergency" by the majority of RNs and MDs; women requesting EC in this setting were most often referred to an outside provider. A similar, more recent phone survey was conducted in Massachusetts' EDs (15). Nurses primarily answered questions about availability of EC, which was reported to be available in 80% of calls.…”
Section: Discussionmentioning
confidence: 99%
“…Since SANE is a community, not hospital-based program, SANE services are not consistently available at all hospitals, even in areas where SANE has a presence. It is the responsibility of emergency departments in NM to provide EC to sexual assault survivors in all instances, regardless of SANE availability.A number of studies have examined the use of emergency contraception when treating victims of sexual assault(8)(9)(10)(11)(12)(13)(14)(15). In 2004, a telephone survey of hospitals in Pennsylvania revealed that only 42% of emergency departments routinely offered EC counseling to victims of sexual assault, while 16% never offered such counseling(10,11).…”
mentioning
confidence: 99%